The Prevalence of BRCA1 and BRCA2 Mutations in Breast Cancer Patients - Piryanka Goindani, Abdul Rehman, Aisha Siddiqa, Berkha Rani, Sona Devi, Aakash Ramchand (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Genetic mutations in BRCA1 and BRCA2 are crucial for breast cancer risk assessment and treatment planning. Methods: This prospective observational study at Jinnah Postgraduate Medical Centre, Pakistan, involved female breast cancer patients aged 18 or older. The sample size calculation was based on a 3.4% prevalence rate of BRCA mutations, aiming for a 95% confidence level. Data on demographic, clinical characteristics, and genetic testing for BRCA mutations were collected and analyzed using SPSS version 23. Results: Among the study participants, 10% exhibited BRCA1 or BRCA2 mutations. The majority were diagnosed at stage 3 tumor development, with invasive ductal carcinoma being the predominant histological type. No significant familial predisposition to breast cancer was noted among the majority. Educational status and ethnicity showed varying associations with BRCA mutation presence. Conclusion: The study highlights a modest incidence of BRCA mutations among Pakistani breast cancer patients, underscoring the importance of genetic testing for risk assessment and targeted treatment. The findings support the need for comprehensive genetic screening programs in Pakistan, considering the diverse demographic and clinical characteristics of the population. Keywords: BRCA mutations, breast cancer, genetic testing, Pakistan, risk assessment, targeted treatment.